(untitled) (Hekima Review, 2016)
The purpose of this article is to evaluate the theological idea of love of neighbour in the light of charity in truth. The evaluation is based on the concept of integral human development, a theme of Caritas in Veritate, the encyclical of Pope Benedict XVI. The article argues that love of neighbour concerns all people created in the image of God. It is the love which defeats all human differences which may cause unnecessary conflicts. In this encyclical, Benedict XVI elaborates the love of neighbour in terms of human integral development. In this perspective, the article maintains that a human person is the centre of concern in the project of integral human development. Promotion of human life and dignity is central in the Church’s Mission towards integral human development